Evidence-Based Guidelines: Tympanostomy Tube Insertion and Adenotonsillectomy - Wilson, Justin D.; Brigger, Matthew T. (Journal of Pediatric Infectious Diseases, 2019)
Myringotomy with tympanostomy tube placement and tonsillectomy (with or without adenoidectomy) are two of the most common procedures performed in the pediatric population. Indications for these surgical treatments are for correspondingly prevalent conditions affecting children, including middle ear and adenotonsillar disease, which are treated by many specialty groups spanning family physicians, pediatricians, emergency care physicians, and otolaryngologists. Despite the common nature of these diseases and respective indicated surgeries, their management has in the past had limited evidence-based guidelines. This article consolidates the most up-to-date evidence from the otolaryngology, pediatric, and infectious disease literature to guide the management with tympanostomy tube insertion and adenotonsillectomy in the pediatric population.
Keywords: tympanostomy; adenotonsillectomy; adenoidectomy; tonsillectomy; otitis media; tonsillar hypertrophy; adenoid hypertrophy; adenotonsillitis; pharyngitis